Reflections on the design of corporate headquarters - Andrew Campbell (Journal of Organization Design, 2020)
The design of corporate headquarters (CHQ) is a specialist and important area of organization design. It is important because of the influence that a CHQ has over the portfolio of businesses it owns. A good CHQ can improve the performance of its businesses. A bad CHQ causes its businesses to perform less well. This article describes the lessons learned from a 30-year career researching, advising, and governing corporate leaders. It covers the reasons why CHQ design is so important, why CHQ design work often also involves strategy work, what activities are needed at the CHQ level, and the problem of subtracted value. The ambition is to help practitioners design better CHQ and help researchers design more relevant research.
Keywords: 650; Corporate headquarters; CHQ; Organization design; Diversified companies; Added value; Subtracted value